Enhanced photochemical formation of active nitrogen species from aqueous nitrate in the presence of halide ions - Zhao, Yilong; Liu, Chengwei; Tu, Xiang; Huang, Wenkai; Liu, Yu; Fu, Hongbo (Frontiers in Environmental Science, 2024)
Field observations have confirmed that halide ions are widely distributed among aero-sols from the marine boundary layer and on the surfaces of ice and snow in polar re-gions. Consequently, the coexistence of halide ions may play a more significant role in nitrate photolysis than previously thought. In this study, we simultaneously measured HONO, NO2, and NO2– in situ to gain a deeper understanding of the coexisting system, including the photogenerated nitrogen products and the effects on nitrate photolysis rates due to enhanced aqueous nitrite and HONO transfer rates by halides. The presence of halides significantly increased the photogenerated nitrogen products across various molar ratios ([X–]/[NO3–]) at pH 3.5. By eliminating oxygen flux, the transformation of primary photogenerated products was affected, resulting in higher concentrations of N(III) as both HONO and NO2–. Experiments involving ·OH scavengers indicated that the attack from ·OH initiated by halides leads to side reactions that enhance nitrate pho-tolysis. Both theoretical calculations and nitrate actinometry were used to determine the photolysis rate of nitrate solutions, which together indicated that the presence of halides enhances nitrate photolysis. A newly developed model was used to determine the HONO transfer rate, finding that the presence of halides ([X–]/[NO3–] = 0.2) enhanced the evaporation of N(III) in solution by factors of 0.68, 0.95, and 1.27 for Cl–, Br–, and I–, respectively. To our knowledge, this is the first determination of halide effects on the mass transfer of HONO. The enhanced nitrate photolysis rate can be attributed to the differential surface effects of halides and parallel reactions initiated via ·OH stemming from nitrate photolysis, with varying rates leading to different quantities of nitrogenous products. Additionally, simultaneous measurements of photoproducts in both gas and condensed phases are recommended to better constrain the rate constants of NO3– pho-tolysis.